In-service Teacher Professional Education Program and the Implementation of Learning Tools in the Merdeka Curriculum - Syofiani, Syofiani; Morelent, Yetti; Azkya, Hidayati (Universitas Jambi, Indonesia, 2024)
This research aimed to describe the understanding of teachers in in-service teacher professional education program [ITPEP] and the implementation of learning tools in the form of teaching modules, teaching materials, student worksheet, learning media, and grid and evaluation. The theory used in this research is the Merdeka Curriculum and learning tools in the Merdeka Curriculum. This descriptive qualitative research describes how ITPEP teachers understand the learning tools. Data were collected using a questionnaire sent via Google Forms because the average of ITPEP teachers Batch III students come from various regions. Furthermore, the data are analyzed using a Likert scale to determine the teachers' understanding of the learning tools in the Merdeka Curriculum. The results indicated More than 85% of teachers participating in the research showed a lack of in-depth understanding of the various components of learning tools and how to apply them effectively in the learning process. The main obstacles faced include the lack of adequate training, limited school infrastructure and facilities, especially access to technology, and difficulty adapting to the change in learning paradigm from a teacher-centered approach to a learner-centered approach.